THE INFLUENCE OF CCTV AGAINST ACTIVITIES STUDENTS IN LEARNING CITIZENSHIP EDUCATION HIGH SCHOOL YP UNILA BANDAR LAMPUNG - Heni Lestiawati; Berchah Piteoewas; Hermi Yanzi (Jurnal Kultur Demokrasi, 2012)
The purpose of this research to explain how The Influence Of CCTV Against Activities Students In Learning Citizenship Education High School YP Unila Bandar Lampung In Academic Year 2012/2013. Research using descriptive method with a sample of 80 respondents using questionnaire data collection and data analysis techniques using Chi quadrat.Keywords: the use of CCTV, learning activities, civic education